The Effect of Talent Management and Work Motivation On Employee Performance with Employee Retention as Intervening Variables in The Public Sector - Permadi, Ramadhani Bagus; Nurhasanah, Siti; Febriani, Rizki; Robbie, R. Iqbal (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The purpose of the study was to determine the effect of talent management and work motivation on employee performance with employee retention as an intervening variable at Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Jombang Regency. The population and sample in this study were all 50 employees using a total sampling technique. Data collection techniques using a questionnaire. The data analysis method used is Partial Least Square (PLS). The results of this study conclude that talent management has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, talent management has a positive and significant effect on employee retention, work motivation has a positive and significant effect on employee retention, employee retention has a positive effect and significantly on employee performance, employee retention is able to mediate positively and significantly the relationship of talent management variables to employee performance and employee retention is able to mediate positively and significantly the relationship of work motivation variables to employee performance.